ADVANCE Trial: PEG-IFN-β-1a Every 2 Weeks Significantly Improved Outcomes over 2 Years in RRMS - Rizzo, Toni (MD Conference Express, 2014)
The 1-year results of the Efficacy and Safety Study of Peginterferon Beta-1a in Participants With Relapsing Multiple Sclerosis [ADVANCE; Calabresi PA et al. Lancet Neurol. 2014] demonstrated superior clinical and magnetic resonance imaging (MRI) outcomes as compared with placebo in patients with relapsing-remitting multiple sclerosis (RRMS). Post hoc analyses showed that significantly more patients treated with peginterferon beta-1a (PEG-IFN-β-1a) versus placebo had no evidence of disease activity (NEDA) at year 1 [Calabresi PA et al. ACTRIMS/ECTRIMS. 2013 (poster P514)]. The aim of this analysis of the ADVANCE trial was to evaluate MRI outcomes and NEDA over 2 years.